Finger-Actuated, Self-Contained Immunoassay Cassettes - Qiu, Xianbo (2009)
The building blocks for an inexpensive, disposable, luminescence-based microfluidic immunoassay cassette are described, and their integration in a point-of-care diagnostic system is demonstrated. Fluid motion in the cassette is driven by depressing finger-actuated pouches. All reagents needed for the immunoassay can be stored in the cassette in liquid form. Prior to use, the cassette consists of two separate parts. A top storage component contains pouches, sealed storage chambers, a metering chamber, and needle seats. The bottom processing component contains connection needles, a mixing chamber, and a detection chamber with immobilized proteins. Subsequent to sample introduction, the storage and processing components are mated. The needles form hydraulic connections between the two parts and, in some cases, close valves. The pouches are then actuated sequentially to induce flow of various reagents and facilitate process operations. The cassette is compatible with different detection modalities. Both a cassette with immunochromatographic-based detection and a cassette with microbead-based detection were constructed and evaluated. The immunochromatographic cassette was used to detect antibodies to HIV in saliva samples. The bead-based cassette was used to detect the proinflammatory chemokine IL-8. The experimental data demonstrates good repeatability and reasonable sensitivity.